Ecuador : Diversification and Sustainable Growth in an Oil - Dependent Country - World Bank (Washington, DC, 2014)
Diversification is important to sustainable economic growth and economic development in an oil-dependent country like Ecuador because it allows the country to be less vulnerable to external shocks. An analysis of diversification in the Ecuadorian economy is needed at this time because (a) the growth has been sluggish despite favorable terms of trade in recent years, and (b) external and fiscal balances are highly vulnerable to shocks in oil prices. This study focuses on the general concept of diversification, including diversification of public revenues, trading partners, and production. It seeks to understand the linkages between the oil and non-oil sectors and offer recommendations on how Ecuador could frame public policy to achieve diversification.